The Concepts of Challenge Based Learning and Creativity Based Learning in the 21st Century - Inkaew, Chamaiporn; Napapongs, Wichai (Journal of Information and Learning [JIL], 2020)
The 21st century learning management requires educators to adapt their thinking to keep pace with the rapid change. This is a positive effect on the learning adaptation of the learners in a variety of learning management concepts that are suitable for facing the challenges change in such circumstances. There are two concepts in this article: challenge base learning and creativity based learning, each of which is able to fulfill the development of the country to transform into a digital society era. This is due to the fact that both concepts encourage learners to solve problems in a real environmental world. It is a challenge for learners to focus on thinking that is new, modern, and useful. All of these factors are fundamental to the development of innovation. This is a response to the national development of science, economy, and industry which makes a significant contribution to global development. Importantly, these two concepts are congruent and promote learning and skill development of the 21st century learners, which are linked to the further development of the global society. However, the successful implementation of this idea depends on goals, needs, and availability including teachers and learners. Therefore, those who adopt these concepts should apply them according to the context so that the use of both learning concepts will be more efficient and effective for the learners.